PHYTOCHEMICAL STUDIES OF THE PETROLEUM ETHER EXTRACT OF THE LEAVES OF Lagerstroemia speciosa Linn - S.M. Mizanur Rahman; Shayla Pervin; Md. Abdul Quader; M. Amzad Hossain (Universitas Gadjah Mada, 2009)
Two new compounds, normal alcohol containing of higher carbons and isomer of β-sitosterol were isolated for the first time from the petroleum extract of the leaves of Lagerstroemia speciosa. The structure of the compound has been established on the basis of UV, IR, 1H-NMR, 13C-NMR and mass spectra and identified as nonanol and isomer of β-sitosterol.